1993
DOI: 10.1080/00140139308967988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded dosages of alcohol on nine computerized repeated-measures tests

Abstract: We report a controlled laboratory validation experiment to provide an empirical sequel to the general background of the development of the Automated Performance Test System (APTS) that was presented in Turnage et al. (1992). The purpose of this study was to index performance deficit against various Blood Alcohol Concentrations (BACs) of small (0.05% BAC), medium (0.10% BAC), and large (0.15% BAC) dosages as well as a placebo (0.00 BAC) condition. Blood alcohol concentrations, measured in four different ways, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…reasoning tests were not generally affected by BACs below 0.080 g/dl, although Heishman et al (1997) and Kennedy et al (1993) reported impairment at BACs of 0.025 g/dl and 0.060 g/dl, respectively. Memory tests, including the Sternberg memory tests, which require subjects to memorize a set of symbols (letters or numbers) and to later determine whether a short sequence of symbols contains the memorized set, were not affected by BACs below 0.060 g/dl.…”
Section: Vigilance Tasks (Figure 3mentioning
confidence: 77%
“…reasoning tests were not generally affected by BACs below 0.080 g/dl, although Heishman et al (1997) and Kennedy et al (1993) reported impairment at BACs of 0.025 g/dl and 0.060 g/dl, respectively. Memory tests, including the Sternberg memory tests, which require subjects to memorize a set of symbols (letters or numbers) and to later determine whether a short sequence of symbols contains the memorized set, were not affected by BACs below 0.060 g/dl.…”
Section: Vigilance Tasks (Figure 3mentioning
confidence: 77%
“…Small sets of letters (typically 4-7 letters) are presented briefly, after which participants are presented with a probe letter and asked to indicate whether the probe letter was included in the presentation set. Alcohol has been shown to increase the number of errors and reaction time (RT) on the Sternberg task, although the effect on RT is not consistently observed (7)(8)(9). In one study testing participants during both the ascending and descending limbs of the blood alcohol concentration curve, the number of errors was impaired on both limbs, whereas RT was impaired only on the ascending limb (7).…”
Section: Working Memorymentioning
confidence: 93%
“…The ® ndings of various studies suggest that alcohol im pairs cognitive performance such as memory, word¯uency and associations (W allgrew and Barry 1970 ), verbal learning (Rosen and Lee 1976 ), vigilan ce (Horne and Gibbons 1991 ), code substitution, choice reaction time (Kennedy et al 1993 ) free recall and recognition (M aylor et al 1990 ) and so on. M aylor and Rabbitt (1987a ) dem onstrated that the rate of forgetting is signi® cantly increased with alcohol.…”
Section: Introductionmentioning
confidence: 98%